2019 - CSA Monitoring: Doyogena Climate-Smart Village (Ethiopia) - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Jarvis, Andy; Recha, John W.M.; Ambaw, Gebermedihin; Tadesse, Meron (2020)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Doyogena Climate Smart Village (Ethiopia) in October 2019.